The Existenza of Cultures in the Age of Globalization: Dialectics of Unity and Disintegration - Sadykova, T.M.; Sapargaliyeva, S.Zh.; Bakirova, A.T. (Karagandy University of the name of acad. E.A. Buketov, 2025)
This article explores the conflicting nature of globalization, focusing on how global integration impacts the preservation of cultural identities. It looks at the push and pull between cultural unification and local traditions in today’s fast-changing world shaped by technology and shifting geopolitics. The analysis draws on the work of S. Huntington “Clash of Civilizations,” F. Fukuyama “The End of History?,” and D. Held’s ideas on global integration. It also brings in perspectives from Russian scholars L.I. Fedorova and P.I. Kasatkin to highlight regional and cultural angles. The study combines theory with real-world examples from China, Russia, and several Islamic countries. These cases show how states may welcome modernization and global cultural influences, yet still reject liberal democratic norms and hold on to traditional values. The findings suggest that globalization doesn’t always result in cultural blending. Instead, it often leads to hybrid forms — where global and local forces collide, coexist, or adapt to each other. The article highlights how cultural resistance and selective adaptation can help societies maintain their uniqueness under global pressure. It also looks closely at the role of identity, memory, and cultural symbols in this process. Overall, the piece argues that globalization isn’t just about dominance or uniformity. It’s a much messier process of negotiation, where cultures reshape themselves, resist certain aspects, and find ways to adapt. In doing so, globalization becomes both a challenge and a chance for deeper intercultural exchange.
Keywords: dialectics; cultural diversity; geopolitical conflicts; traditional values; hybrid models; integration; localization; national uniqueness; cultural globalization